2012
DOI: 10.5194/amt-5-927-2012
|View full text |Cite
|
Sign up to set email alerts
|

Validation of ACE and OSIRIS ozone and NO<sub>2</sub> measurements using ground-based instruments at 80° N

Abstract: Abstract. The Optical Spectrograph and Infra-Red Imager System (OSIRIS) and the Atmospheric Chemistry Experiment (ACE) have been taking measurements from space since 2001 and 2003, respectively. This paper presents intercomparisons between ozone and NO 2 measured by the ACE and OSIRIS satellite instruments and by groundbased instruments at the Polar Environment Atmospheric Research Laboratory (PEARL), which is located at Eureka, Canada (80 • N, 86 • W) and is operated by the Canadian Network for the Detection … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 63 publications
1
50
1
1
Order By: Relevance
“…Tests with a preliminary version of the next generation ACE-FTS retrievals (version 3.0) have shown that the slight positive stratospheric bias has been removed." Adams et al (2012) additionally present an intercomparison of ACE ozone profiles (both versions 2.2 and 3.0) against ground-based observations at Eureka, confirming that the new ACE-FTS v3.0 and the validated v2.2 partial ozone columns are nearly identical, with mean relative difference of 0.0 ± 0.2 % for v2.2. minus v3.0.…”
Section: Ace-fts Satellite Datamentioning
confidence: 66%
“…Tests with a preliminary version of the next generation ACE-FTS retrievals (version 3.0) have shown that the slight positive stratospheric bias has been removed." Adams et al (2012) additionally present an intercomparison of ACE ozone profiles (both versions 2.2 and 3.0) against ground-based observations at Eureka, confirming that the new ACE-FTS v3.0 and the validated v2.2 partial ozone columns are nearly identical, with mean relative difference of 0.0 ± 0.2 % for v2.2. minus v3.0.…”
Section: Ace-fts Satellite Datamentioning
confidence: 66%
“…The ozone air mass factors produce total columns (Hendrick et al, 2011), while the NO 2 air mass factors produce partial columns from 17 km to the top of the atmosphere (Appendix A of Adams et al, 2012a). On average, errors of 6.0 % for ozone, 19 % for NO 2 -vis and 19 % for NO 2 -UV were calculated for April/May GBS measurements.…”
Section: Doas Ozone and Nomentioning
confidence: 99%
“…The GBSs are part of the Network for the Detection of Atmospheric Composition Change (NDACC) and their Eureka ozone and NO 2 datasets are described in detail by Adams et al (2012a). Measurements from the two GBS instruments are nearly identical and therefore were combined into a single GBS dataset.…”
Section: Doas Ozone and Nomentioning
confidence: 99%
See 2 more Smart Citations